Chemo-Mechanical Evaluation of Asphalt Mixtures Reinforced With Synthetic Fibers - Bueno, Moises; Poulikakos, Lily D. (Frontiers in Built Environment, 2020)
The use of additives in asphalt mixtures has been an important option in order to prolong the durability of the road infrastructure. Several works have reported that the utilization of synthetic fibers (e.g. plastic fibers) visibly enhance the overall mechanical performance of asphalt mixtures. The objective of this experimental study is to understand the physicochemical mechanisms leading to this superior response. With this in mind, two synthetic fibers were selected in order to analyze their effect within a conventional dense asphalt mixture used in Switzerland. The mechanical performance of the experimental mixtures along with the thermal properties of the fibers were evaluated. First, it was concluded that the fiber reinforced asphalt mixtures could perform similarly to the standard mixtures prepared with polymer modified binder. In addition, it was confirmed by imaging analysis that the reinforcing effect was associated to the physical presence of the fibers within the asphalt matrix.